Avaliação das forças de atrito de fios ortodônticos de níquel-titânio e aço inoxidável em braquetes auto-ligados ativos - Ana Cristina Rodrigues Antunes de Souza (2011)
The aim of this study was to evaluate and compare the frictional forces of stainless steel and rounded stainless steel wires, NiTi superelastic and NiTi shape memory wires, during sliding movement by stainless steel self-ligating brackets and ceramic self-ligating brackets. The wires and brackets were characterized before the tests and after that, the wiresurfaces were evaluated. The results showed that stainless steel self-ligating brackets were composed by austenitic stainless steel whereas the covers were composed by NiCrCo. Ceramic self-ligating brackets were composed by aluminum oxide whereas the covers werecomposed by Aluminum and Rhodium. Stainless steel wires were composed by austenitic stainless steel and NiTi wires exhibited Ni and Ti in equal proportions, with phase at room temperature and superelasticity. All wires and brackets showed irregular surfaces.Ceramic self-ligating brackets exhibited higher microhardness than stainless steel selfligating brackets. The stainless steel and NiTi wires showed similar microhardness inside groups, but first ones microhardness were higher than the seconds. All slots of brackets andall wires showed dimension reduction. The friction forces tests revealed media forces for sliding wires by ceramic self-ligating brackets were higher than to stainless steel ones. No statistic differences were observed between the media forces for stainless steel wires slidingby both brackets. Higher media forces to NiTi wires were obtained when compared to the stainless steel wires to both brackets. No differences of media forces between two NiTi wires sliding by ceramic self ligating brackets, nevertheless the media forces for superelastic NiTi wire were higher then to the shape memory NiTi wire when sliding by stainless steel self-ligating brackets. All wires after frictional forces tests exhibited more surface irregularities.